PENGARUH LEVERAGE, LIKUIDITAS, SIZE, PERTUMBUHAN LABA DAN IOS TERHADAP KUALITAS LABA - Sadiah, Halimatus; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This main aims of this study is to test whether the capital structure, liquidity, firm size, profit growth and Investment Opportunity Set (IOS) to the profit quality. The population is all manufacturing companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been done by using purposive sampling which is the selection of samples which is done by using certain criteria and 58 manufacturing companies during the 2010-2013 periods have been obtained as samples. The data is the secondary data which has been obtained from Indonesian Stock Exchange (www.idx.co.id) and Indonesian Capital Market Directory (ICMD). The result of the research shows that: (1) Capital structure does not have any significant influence to the profit quality and it has negative coefficient which indicates that the correlation is not unidirectional. (2) Liquidity does not have any significant influence to the profit quality but it has positive coefficient which indicates unidirectional correlation. (3) Firm size has significant influence to the profit quality and it has positive coefficient which indicates unidirectional correlation. (4) Profit growth has significant influence to the profit quality and it has positive coefficient which indicates unidirectional correlation. (5) Investment opportunity set has significant influence to the profit quality and it has positive coefficient which indicates unidirectional correlation.Keywords: Profit Quality, Capital Structure, Liquidity, Firm Size, Profit Growth and Investment Opportunity Set (IOS).